Patterns of Symbolic Interaction Communication in the Online Ojek Community: Qualitative Descriptive Study - Utami, E. W. Puput Wahyu; Kustiawan, Unggul (Peneliti.net, 2024)
Presently, service quality manifests in the form of technology known as Self-Service Technology (SST), which has a significant impact on how customers interact with a company. The aim of this research is to explore the factors influencing customer perception of SST Qual concerning customer satisfaction and trust, leading to repurchase intention and e-word of mouth in fast-food restaurant customers. This study focuses on internationally recognized brands in Indonesia, namely McD, Pizza Hut, KFC, A&W, and Burger King, and examines the influence of SST Qual through social media platforms such as Facebook, Instagram, Twitter, and TikTok, which are utilized by customers. This is the outcome of advancements made from prior studies on Indonesian consumers of online retail businesses. It is intended that the research's contribution will offer useful marketing tactics for consumers of the brands under study in addition to information at the theoretical and scientific level of marketing management. The present study employed a survey approach for data collection, whereby online questionnaires were disseminated to potential respondents, who were chosen using purpose sampling among patrons of international restaurants in Indonesia. For analysis using factor analysis and structural equation modeling (SEM) with the smartPLS application. The findings from this study are that SST Qual is the main driver in increasing and forming customer satisfaction and customer trust which will increase and retain customers so that repurchase intention can be achieved through encouraging eWOM from other consumers